Development of Melodic Intonation Therapy-Audio in Improving the Speaking Ability of Stroke Patients - Cahyati, Yanti; Rosdiana, Ida (Poltekkes Kemenkes Palu, 2024)
Introduction: This research aims to see the effect of modifying Melodic Intonation Therapy (MIT) and Dhikr Asmaul Husna in audio form on the speaking ability of stroke patients. Aphasia is a disability problem experienced by stroke patients and can become persistent, reducing their quality of life. Efforts are needed to improve speaking ability so patients can continuously and independently carry out post-stroke speech exercises at home. The results showed that MIT gave better results in improving the speech ability of stroke patients. In the MIT method, patients repeat words spoken by nurses or family members using musical elements while speaking. Methods: This type of research is quantitative with a quasi-experimental design pre and post-test. Researchers carry out interventions using media in the form of Melodic Intonation Therapy Audio (MIT-A), which results from research development. This study's population is stroke patients treated at Dr. Soekardjo Tasikmalaya Hospital, Prasetya Bunda Hospital, and Banjar City Hospital. The sample consisted of 33 respondents from three Tasikmalaya and Banjar City hospitals. Exercises start when the patient is treated and continue to be done at home. Speech ability was evaluated using the TADIR method (Aphasia Test for Diagnostics and Rehabilitation), assessed before the intervention and at the first control visit. The intervention was carried out for one month. The hypothesis in this study is that there is a difference in the average score of speech ability before and after the intervention. The t-dependent test tests the difference in TADIR scores before and after training. Results: The study showed a difference in the average TADIR score before and after training (p-value 0.000). This indicates that speech training using MIT-Audio has a significant effect on the speaking ability of stroke patients. Conclusion: The results of this study conclude that speech training through modified MIT in audio form improves the speaking ability of stroke patients who experience aphasia. The researcher recommends that future researchers apply this speech training media by differentiating the type of aphasia experienced by the patient.